Trusted-Region Subsequence Reduction for Designing Resilient Consensus Algorithms - Zhai, Yang; Liu, Zhi-Wei; Ge, Ming-Feng; Wen, Guanghui; Yu, Xinghuo; Qin, Yuzhen (IEEE transactions on network science and engineering, 2021)
Existing resilient consensus algorithms are mainly developed based on the mean subsequence reduced (MSR) method, which relies on the assumption that there exist at most f malicious agents in the entire network or each neighborhood (i.e., f -total or f -local model). However, in some practical cases, it may be impossible to estimate an appropriate upper bound on the number of malicious agents. This paper proposes a novel method, called trusted-region subsequence reduction (TSR), for designing resilient consensus algorithm without the f -total/local model assumption. The main idea of the TSR method is to filter out the received information beyond a dynamic trusted region, determined by the current relative positions of the neighboring trusted nodes. Based on the TSR method, we design a sampled-data resilient consensus algorithm for double-integrator multi-agent networks. A necessary and sufficient graph-theoretic condition is obtained to achieve resilient consensus. Finally, simulations are conducted to illustrate the effectiveness of the proposed algorithm and the faster convergence rate of the TSR-based algorithm than the classical MSR-based algorithm.